Analysis of management system for patients with acute stroke in community. - Phonphithak, Chokchai; Kongtaln, Orasa; Piyabanditkul, Lukawee (Thai Journal of Nursing, 2022)
This qualitative study aimed to analyze the management system of stroke patients in community. Data were collected through in-depth interviews from 33 cases including stroke patients, relative’s caregivers, and people involved in the care of stroke patients in community. Data were analyzed by content analysis method. The results of this study provided the management of the patient in the acute phase, the people who play an important role in the decision to refer patient to hospital for treatment under the condition of perceived symptoms, the severity of the disease, personal factors, health service system and the context of area in community, are the patient himself, his relatives, or those who witnessed the incident while the patient was symptomatic. In the period of continuous care in community, it was found that in addition to the patient himself and his relatives who played a role in caring for and rehabilitating the patient, there are other people involved in community to take part in helping support, health services welfare arrangement and public health policy support. The rapid recognition of symptoms and severity of the disease affects the timely treatment of stroke patients through the Stroke Fast Track. In the period of continuous care in community, the ongoing and effective management of the patients themselves, their caregivers, and those involved in the care of patients in community it plays an important role in promoting the rehabilitation of the patient's physical condition.